Developing a self-assessment tool for English language teachers. (September 2019) - Borg, Simon; Edmett, Adam
In the context of increasing global interest in teacher evaluation, this article describes the development of a self-assessment tool (SAT) for teachers of English and analyses responses to it by 1, 716 teachers from around the world. One feature of respondents' self-assessments was that they were mostly positive, and this issue is discussed in relation to concerns about the accuracy of self-assessed competence more generally. Teachers also provided feedback on the tool itself and their comments on its relevance, clarity, coverage and value were mostly positive too. The teachers did, though, suggest ways in which the SAT could be developed further, and a number of design enhancements are discussed. Two particular challenges highlighted by the results of this study are also considered: the feasibility of developing a self-assessment tool that teachers of English in all contexts can use, and the extent to which teachers are able to assess their competence without reference to the specific circumstances in which they work. The potential for further research around the SAT is also noted, particularly in terms of how it can be combined with classroom observations to provide a more robust overall picture of what teachers are able to do.